2020
DOI: 10.1088/1755-1315/447/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the river-based tourism product for Muar River: A tourism opportunity spectrum (TOS) approach

Abstract: River-based tourism product development is regarded as one of the critical segments that focus on proper physical, social, and economic expansion. To date, the lack of depth and concern is tapped into this market by either scholars or stakeholders accordingly. Currently, a part of the local plan for Muar development is envisioned towards developing and promoting the tourism industry. However, the primary challenge of river-based tourism is maximising the usage and livability of its waters and natural resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In the review of economic studies, i.e., Wheaton andThompson (2020b, 2020a), with direct and straightforward statistical methods, it was found that they tend to prove density influences the spread of the pandemic. The same case happens in sources in geographical studies, i.e., Rahman et al (2020) and Ramírez-Aldana et al (2020), which confirmed the spatial (density of population) factor is correlated significantly to the COVID-19 spread. In this case, the geographical modelling studies tend to generalise the spatial only in two-dimensional views, thus ignoring the fact that density usually happens in a vertical dimension.…”
Section: Reviews On Scholarly Articles Related To Density and Covid-19supporting
confidence: 66%
See 1 more Smart Citation
“…In the review of economic studies, i.e., Wheaton andThompson (2020b, 2020a), with direct and straightforward statistical methods, it was found that they tend to prove density influences the spread of the pandemic. The same case happens in sources in geographical studies, i.e., Rahman et al (2020) and Ramírez-Aldana et al (2020), which confirmed the spatial (density of population) factor is correlated significantly to the COVID-19 spread. In this case, the geographical modelling studies tend to generalise the spatial only in two-dimensional views, thus ignoring the fact that density usually happens in a vertical dimension.…”
Section: Reviews On Scholarly Articles Related To Density and Covid-19supporting
confidence: 66%
“…The geographical analysis generalised the spatial in a twodimensional view and potentially ignored that density is counted vertically in reality. Rahman et al (2020) Data at the district level in Bangladesh were analysed through a spatial regression model (SRM).…”
Section: Ramírez-aldana Et Al (2020)mentioning
confidence: 99%
“…Muar features its strategic location at the mouth of Muar River in a new river-based tourism development project proposal for the rural town of Panchor. According to Rahman et al (2020) and Shah (2018), this is potentially the tourism product that could help Muar achieve its tourism development target.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still a lot more to be done around the Muar River. Limited focus and recognition has been given to the importance of the river, and there are also limited studies being done on the potential sites for tourism development around the river despite it being a river that has large potential for the development of tourism products [33]. With this research, the vacuum is addressed strategically, where geographically the river and the area along the river is given an official entity which we proposed to be named as Muar River Valley (MRV) which also includes the materialization of the MRV concept, where tourists are able to feel, experience or even buy things such as souvenirs or even pay for the participation in tour packages relating to nature tourism in Muar River Valley.…”
mentioning
confidence: 99%